Anti-cyclic citrullinated peptide antibodies in rheumatoid arthritis and Behcet's disease - Koca, Suleyman Serdar; Akbulut, Handan; Dag, Sait; Artas, Hakan; Isik, Ahmet (Tohoku Univ Medical Press, 2007)
Rheumatoid arthritis (RA) is associated with progressive joint destruction and disability. Early diagnosis of RA is important, since early and aggressive treatments lead to a better outcome. Circulating autoantibodies are a serological hallmark of systemic rheumatic diseases. More recently, antibodies directed to a cyclic citrullinated peptide, anti-CCP antibodies, have been established as specific diagnostic and prognostic tools for RA. The aims of this study were to assess the diagnostic and radiological prognostic value of the anti-CCP antibody in Turkish patients with RA (n = 97) and those with Behcet's disease (131)) (n = 46). The study also included 35 healthy controls. Anti-CCP antibodies were measured by ELISA, and radiological damage was evaluated by using modified Larsen scoring. In the RA group, sensitivity and specificity were 80.4% and 93.5% for rheumatoid factor (RF), and 74.2% and 97.8% for anti-CCP antibody, respectively. RF was positive in 3 BD patients (6.5%) and in one of the controls (2.9%). In contrast, anti-CCP antibodies were detected in one BD patient (2.2%), but not in the control subjects. Deformed joint counts and radiographic scores were higher in anti-CCP antibody-positive RA patients (n = 72) than those in anti-CCP antibody-negative patients (n = 25) (p < 0.05). Moreover, anti-CCP antibody titer correlated with deformed joint count (r = 0.224, p < 0.05) and radiographic score (r = 0.308, p < 0.05). This study indicates the diagnostic and prognostic utility of anti-CCP antibodies in Turkish patients with RA. Importantly, anti-CCP antibodies are not associated with BD.
Keywords: rheumatoid arthritis; Behcet's disease; anti-cyclic citrullinated peptide antibody; radiological progression